Plano de logística sustentável para empresas de transporte - (:unkn) unknown (Universidade Brasil, 2020)
Due to the importance for companies to pursue ESG (Environmental, Social and Governance) practices in order to be more responsible in relation to environmental, social and governance issues and improve their reputation in the market, it is imperative to develop methodologies that facilitate achieving these goals. Therefore, the objective of this work was to develop the Company Sustainability Diagnosis System (DISE System) and apply it to assist a transport company in Fernandópolis - SP in the elaboration of their Sustainable Plan for Transport Logistics (SPTL). The methodology used for developing the system of diagnosis and classification of companies was based on the ten principles of the UN Global Compact. The system, which was called the Company Sustainability Diagnosis System or “DISE” System, allows classifying the company's level of sustainability from a scoring system, obtained from surveys about the company. Scores are determined by criteria and calculated by simple equations. After its development, its application was carried out in a transport company based in Fernandópolis - SP, for which it was possible to classify it as "moderate sustainability" and propose an action plan that will compose their Sustainable Plan for Transport Logistics (SPTL), with goals of achieving sustainability in 2026. Based on the results, it was concluded that the DISE System (Company Sustainability Diagnosis System) made it possible to diagnose, in an easy and objective way, a transport company in the municipality of Fernandópolis - SP. As a result, a technical instruction manual for the application of the DISE system was also elaborated for companies in general, assisting them in ESG practices, in improving their reputation in the market and in their pursuit of sustainability.
Keywords: Pacto Global da ONU; ESG (Environmental, Social and Governance); Desenvolvimento sustentável; Legislação Ambiental